Effects of low doses of carbendazim or iprodione either separately or in mixture on the pubertal rat seminiferous epithelium: An ex vivo study. (December 2017) - Durand, Philippe; Martin, Guillaume; Blondet, Antonine; Gilleron, Jérôme; Carette, Diane; Janczarski, Stéphane; Christin, Emilie; Pointis, Georges; Perrard, Marie-Hélène
Abstract: It has been shown that non-cytotoxic doses of Carbendazim (CBZ), a broad-spectrum benzimidazole fungicide, possess endocrine-disrupting (androgen-like) actions, ex vivo, on the pubertal rat seminiferous epithelium. Iprodione (IPR), a dicarboximide fungicide, is also known to be an endocrine-disrupter (anti-androgen). The effect of a mixture of these two pesticides was investigated in the validated rat seminiferous tubule culture model. Cultures were performed in the absence or presence of CBZ 50 nM or IPR 50 nM either alone or in mixture (Mix), over a 3-week period. Mix exerted a dramatic effect on two proteins (Connexin 43 and Claudin-11) of the blood-testis barrier and possessed similar effects to IPR on some germ cell populations. The presence of IPR together with CBZ (Mix) cancelled the effect of CBZ on the increase of the androgen-dependent TP1 and TP2 mRNAs and on the decrease of ERα, ERβ mRNAs. Nevertheless, CBZ alone or IPR alone or Mix induced toxicity on spermatogenesis resulting in a decrease of round spermatids (the precursors of spermatozoa). These results strongly suggest that, even at these low concentrations, the effects of IPR and of CBZ are not solely dependent on their respective anti-androgenic and androgen-like effects and should involve several mechanisms of action. Highlights: Carbendazim or Iprodione, alone or in mixture, disrupted spermatogenesis ex vivo Mixture possessed similar effects to Iprodione on all germ cell populations. Carbendazim or Iprodione, either alone or in mixture, induced a decrease of spermatids. The results are not solely related to endocrine disrupting effects of these products.